Impact of Ligustrum lucidum on the soil seed bank in invaded subtropical seasonally dry woodlands (Córdoba, Argentina) - Ferreras, Ana Elisa (2015)
The impact of invasive species on below ground flora may differ from that on the above ground vegetation. Recent reviews of invaded and native communities emphasize the need for more comprehensive information on the impacts of plant invasion on soil seed banks. Ligustrum lucidum is one of the most important invasive woody species in several ecosystems of Argentina; however, its impact on soil seed bank communities has not been studied. Here we analyzed differences in species richness, total seed density and species composition (total, native and exotic species) in the soil seed bank of native and invaded woodlands, in two different seasons. We also analyzed differences in similarity between standing vegetation and soil seed banks of both woodland types. The study was carried out in the Chaco Serrano woodlands of Córdoba, central Argentina. Our main results indicate differences in L. lucidum woodland composition and a reduction in both richness and total density of species in the soil seed bank compared to the native woodlands, independently of the sampling season. Moreover, a higher abundance of certain exotic species in the soil seed bank was observed in L. lucidum woodlands, particularly in spring. Finally, low similarity between soil seed bank and the established vegetation was observed in both woodland types. From a management perspective, it seems that passive restoration from soil seed banks of L. lucidum might be coupled with active addition of some native woody species and control of other exotic species.